INTEGRATED MODEL FOR ORGANIZATIONAL TRANSFORMATION IN BUSINESS PROCESS REENGINEERING (Journal of Information and Communication Technology, 2007)
This paper presents a pilot study implementing business process engineering where integrated model was used for business transformation analysis. Business process reengineering is a process that contributes to organizational transformation which will redesign the business processes and management to achieve dramatic improvement in business performance. A model that can bridge the gap between business and technical view is needed in the reengineering processes such that it can be easily translated from both business and technical perspective. This study demonstrate the feasibility of using model as technique in generating reengineering solution for organizational transformation in a human resource department of a wholesale company. Evaluation by users including the human resource officer shows a high satisfaction and improvement in the prototype representing new wok processes develop using Lotus Notes.